Pure metal / high-entropy amorphous alloy nano multilayer film with three-dimensional interface and preparation method of pure metal / high-entropy amorphous alloy nano multilayer film

By forming a nano-multilayer film with three-dimensional interfaces in high-entropy amorphous alloys, magnetron sputtering and vacuum heat treatment technology are used to solve the fracture problem of high-entropy amorphous alloys during deformation, significantly improving the strength and plastic toughness of the material.

CN119615064APending Publication Date: 2025-03-14XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202510110028.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

High-entropy amorphous alloys are prone to form shear bands and fail to break during plastic deformation, and their deformation mechanism is difficult to regulate, resulting in insufficient mechanical properties.

Method used

Magneto-controlled sputtering technology is used to alternately deposit pure metal Cu layer and high-entropy amorphous alloy layer in a vacuum environment to form a nano-multilayer film with a three-dimensional interface, and the interface morphology is regulated through vacuum heat treatment to improve dislocation storage capacity and heterogeneous deformation stress.

Benefits of technology

By forming a three-dimensional interface, the plug building and orderly arrangement of dislocations are significantly enhanced, the strength and plastic toughness of the material are improved, and the fracture problem of high-entropy amorphous alloys is effectively solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615064A_ABST
    Figure CN119615064A_ABST
Patent Text Reader

Abstract

The invention discloses a pure metal / high-entropy amorphous alloy nano multilayer film with a three-dimensional interface and a preparation method, and belongs to the field of metal surface modification.The nano multilayer film comprises crystal layers and amorphous layers which are alternately stacked, the crystal layers are of a single-phase face-centered cubic structure, crystal grains are columnar crystals growing in the deposition direction and penetrating through component layers, and the amorphous layers are of a single-phase face-centered cubic structure. The amorphous layer keeps a long-range disordered structure, and an interface between the crystal layer and the amorphous layer is of a three-dimensional structure; different from a two-dimensional sharp interface, a three-dimensional interface has certain strength, movement of dislocation in the area is subjected to stress, and then the current situation that dislocation completes slippage, namely annihilation, is changed. According to the preparation method, dislocation is orderly arranged near a three-dimensional interface, so that accumulation occurs, heterogeneous deformation stress is remarkably enhanced through long-range ordered dislocation arrangement, and the strength of the material is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal surface modification, in particular to a pure metal / high entropy amorphous alloy nano multilayer film with a three-dimensional interface and a preparation method thereof. Background Art

[0002] In recent years, high entropy amorphous alloys have attracted widespread attention due to their unique microstructure and excellent physical and mechanical properties. High entropy amorphous alloys contain 4 or more elements, and the content of each component element is usually between 5% and 35%. They have a series of effects such as high entropy effect and hysteresis diffusion effect. However, their long-range disordered structure makes them lack deformation carriers. Once plastic deformation begins, shear bands will quickly form and then fracture and fail. Therefore, how to regulate the deformation mechanism of high entropy amorphous alloys to optimize their mechanical properties is a research hotspot and challenge in this field.

[0003] Crystal / amorphous multilayers have been widely used due to their excellent plasticity and toughness and unique shear-slip properties. Alternating the deposition of face-centered cubic metals and high-entropy amorphous alloys to form multilayer films can reduce the geometric size of the amorphous, effectively inhibit the formation of shear bands, and simultaneously improve the strength and plasticity of the material. However, the two-dimensional sharp crystal / amorphous interface has poor dislocation storage capacity, a small number of dislocation pileups during cyclic loading, and is significantly less capable of generating heterogeneous deformation stress and strengthening the soft phase than the crystal / crystal interface. In addition, how to make up for the reduction in strength caused by the decrease in the percentage of twins in the range above the detwinning temperature of face-centered cubic metals and below their annealing twin growth temperature remains to be solved. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a pure metal / high entropy amorphous alloy nano-multilayer film with a three-dimensional interface and a preparation method, thereby realizing the preparation of a pure metal / high entropy amorphous alloy nano-multilayer film with a three-dimensional interface.

[0005] The present invention is achieved through the following technical solutions: In the first aspect, the present application provides a pure metal / high entropy amorphous alloy nano-multilayer film with a three-dimensional interface, comprising crystalline layers and amorphous layers alternately stacked, the crystalline layers are a single-phase face-centered cubic structure, the grains are columnar crystals that grow along the deposition direction and penetrate the component layers, the amorphous layers maintain a long-range disordered structure, and the interface between the crystalline layers and the amorphous layers is a three-dimensional structure.

[0006] Preferably, the bottom layer of the nano multilayer film is a crystalline layer, and the surface layer is an amorphous layer.

[0007] Preferably, the thickness of the crystal layer and the amorphous layer is equal, and the layer thickness is 5 nm to 150 nm.

[0008] Preferably, the crystalline layer is copper, and the amorphous layer is FeCoCrNiBSi alloy.

[0009] In a second aspect, the present application provides a three-dimensional interface pure metal / high entropy amorphous alloy nano multilayer film, comprising the following steps: Step 1, cleaning the substrate surface; Step 2: In a vacuum environment, a pure metal target and a high entropy amorphous alloy target are alternately used to perform DC magnetron sputtering on the substrate, and after cooling, a deposited pure metal / high entropy amorphous alloy nano multilayer film is obtained; The sputtering power is 200 W, the deposition gas pressure is 0.8-1 Pa, the sputtering time of the pure metal target in each sputtering cycle is 17s-510s, and the sputtering time of the high entropy amorphous alloy target is 40s-1200s; Step 3: vacuum annealing the obtained nano multilayer film to obtain a pure metal / high entropy amorphous alloy nano multilayer film with a three-dimensional interface.

[0010] Preferably, the cleaning process includes cleaning the surface of the substrate and removing an oxide film on the surface. Preferably, during the magnetron sputtering, the rotation speed of the silicon substrate is 15 r / min.

[0011] Preferably, the vacuum annealing method is as follows: The temperature was gradually raised to 423-513 K, kept at that temperature for 1 h, and then cooled to room temperature in the furnace.

[0012] Preferably, the heating rate is 175-200 K / h.

[0013] Preferably, the pure metal target is a copper target, and the high entropy amorphous alloy target is a FeCoCrNiBSi alloy target.

[0014] Compared with the prior art, the present invention has the following beneficial technical effects: The present application provides a method for preparing a three-dimensional interface pure metal / high entropy amorphous alloy nano multilayer film. In the sputtering process, magnetron sputtering technology is used to alternately deposit metal Cu targets and high entropy amorphous alloy targets, both using a DC power of 200 W, a low operating temperature, and amorphous structures are maintained, and the thickness of the pure metal layer and the high entropy amorphous alloy layer can be effectively regulated by the deposition time. Naturally cooled to room temperature in a high vacuum chamber, the peeling caused by the difference in thermal expansion coefficients between the interlayers of the film members and the film base is effectively avoided. At the same time, the film is prevented from being oxidized when in contact with air under high temperature, so that the deposited atoms are fully diffused to form a metal / high entropy amorphous alloy nano multilayer film; the present application is regulated by heat treatment, so that the pure metal / high entropy amorphous alloy nano multilayer film with a positive mixing enthalpy interface is mixed on the nanoscale, forming a medium-range ordered crystal / amorphous three-dimensional interface, and when the dislocation is emitted from the dislocation source and completes the slip in the crystal layer, it will reach the three-dimensional interface. Different from the sharp two-dimensional interface, the three-dimensional interface has a certain strength. The movement of dislocations in this area will be affected by stress, which changes the status quo that dislocations are annihilated after completing slip. The dislocations are arranged in order near the three-dimensional interface, and then piled up. The long-range orderly arrangement of dislocations significantly enhances the heterogeneous deformation stress and effectively improves the strength of the material.

[0015] Furthermore, during the vacuum heat treatment process, the most suitable annealing temperature, heating rate and holding time were selected through reasonable process design, which effectively reduced the risk of peeling caused by thermal stress caused by modulus mismatch. In addition, the extremely high vacuum degree during the annealing process effectively avoided the oxidation of the film. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 This is a schematic diagram of the structure of the nano multilayer film of the present invention; Figure 2 XRD patterns of the nano multilayer films of Examples 1 to 6; Figure 3 A 10 nm thick Cu / Fe layer with a three-dimensional interface prepared by magnetron sputtering combined with vacuum heat treatment 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 Plane SEM photo of nano-multilayer film; Figure 4 A 10 nm thick Cu / Fe layer with a three-dimensional interface prepared by magnetron sputtering combined with vacuum heat treatment 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 Low-magnification TEM image of the cross section of the nano-multilayer film. The upper right corner is the selected area electron diffraction (SADP) image corresponding to the area. Figure 5 A 10 nm thick Cu / Fe layer with a three-dimensional interface prepared by magnetron sputtering combined with vacuum heat treatment 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 High-magnification TEM photos of the cross section of the multilayer film and the corresponding FFT graph; Figure 6 A 100 nm thick Cu / Fe layer with a three-dimensional interface prepared by magnetron sputtering combined with vacuum heat treatment 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 Plane SEM photo of nano multilayer film; Figure 7 A 100 nm thick Cu / Fe layer with a three-dimensional interface prepared by magnetron sputtering combined with vacuum heat treatment 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 A low-magnification TEM image of the cross section of the nano-multilayer film. The upper right corner is the selected area electron diffraction (SADP) image corresponding to the area; Figure 8 A 100 nm thick Cu / Fe layer with a three-dimensional interface prepared by magnetron sputtering combined with vacuum heat treatment 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 High-magnification TEM photos of the cross section of the nano-multilayer film and the corresponding FFT images; Fig. 9 Cu / Fe with two-dimensional interface and three-dimensional interface 15.6 Co 14.4 Cr 15.9 Ni 14.1B 23 Si 17 Nano multilayer film hardness comparison chart; Fig.10 Cu / Fe with two-dimensional interface and three-dimensional interface 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 Comparison of heterogeneous deformation stress of nano-multilayer films. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.

[0019] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0020] Although the existing pure metal / amorphous nano-multilayer films have good strain compatibility and unique shear-slip properties compared to pure metal / pure metal nano-multilayer films, when the dislocations emitted by the crystal layer reach the crystal / amorphous interface, they will be absorbed and annihilated by the amorphous layer as a dislocation trap, and no effective accumulation can be formed at the interface, making the heterogeneous deformation stress significantly smaller than that of the pure metal / pure metal nano-multilayer films, and their contribution to the strength is low. In addition, the crystal / twin interface contributes to the heterogeneous deformation stress measured for the low stacking fault energy metal Cu. After detwinning, the heterogeneous deformation stress and strength will be further reduced. Based on the above problems, the present application proposes the following nano-multilayer film.

[0021] A pure metal / high entropy amorphous alloy nano-multilayer film with a three-dimensional interface comprises crystal layers and amorphous layers alternately stacked, the crystal layers are single-phase face-centered cubic structures, the grains are columnar crystals that grow along the deposition direction and penetrate the component layers, the amorphous layers maintain a long-range disordered structure, and the interface between the crystal layers and the amorphous layers is a three-dimensional structure.

[0022] The bottom layer of the pure metal / high entropy amorphous alloy nano multilayer film is a crystal layer, and the surface layer is an amorphous layer.

[0023] The thickness of the crystal layer and the amorphous layer is equal, and the layer thickness is 5nm to 150nm.

[0024] The crystal layers of the nano multilayer film are all single-phase face-centered cubic structures, and no intermetallic compounds are generated. The grains are columnar crystals that grow along the deposition direction and penetrate the component layers, and nano twins are rare in the grains. The amorphous layer maintains a long-range disordered structure, and there are no particles generated by crystallization in the layer. The crystal / amorphous interface is a three-dimensional structure rather than a two-dimensional structure commonly seen in positive mixing enthalpy nano multilayer films.

[0025] A method for preparing a pure metal / high entropy amorphous alloy nano multilayer film with a three-dimensional interface comprises the following steps: Step 1: Clean and dry the surface of the substrate.

[0026] The substrate is a silicon substrate, and the cleaning method is to first polish a single side of the silicon substrate, and then ultrasonically clean the polished silicon substrate in acetone and anhydrous ethanol for at least 10 minutes, respectively, and then dry it.

[0027] In order to improve the bonding strength between the film and the substrate, the oxide film on the surface of the dried substrate is removed. Specifically, the dried silicon substrate is immersed in a hydrofluoric acid aqueous solution for at least 5 minutes and then dried. The concentration of the hydrofluoric acid aqueous solution is 41 wt.%.

[0028] Step 2: In a vacuum environment, a pure metal target and a high entropy amorphous alloy target are alternately used to perform DC magnetron sputtering on the substrate, and after cooling, a deposited pure metal / high entropy amorphous alloy nano multilayer film is obtained; The pure metal target is a Cu target, the high entropy amorphous alloy target is a FeCoCrNiBSi alloy target, the purity of the Cu target is not less than 99.99 wt.%, and the purity of the FeCoCrNiBSi alloy target is not less than 99.95 wt.%.

[0029] During the DC magnetron sputtering process, the chamber vacuum is maintained at 10 -4 Pa, both pure metal targets and high entropy amorphous alloy targets were sputtered by DC sputtering, with a sputtering power of 200 W, a deposition gas pressure of 1 Pa, and a silicon substrate rotation speed of 15 r / min.

[0030] A pure metal layer is first deposited on the silicon substrate, and then a high entropy alloy layer is deposited to increase the bonding strength between the multilayer film and the substrate. The metal layer and the high entropy alloy layer are then deposited alternately. After sputtering is completed, the last layer is a high entropy alloy layer. The sputtering time of the Cu target in each sputtering cycle is 17s-510s, and the sputtering time of the FeCoCrNiBSi alloy target is 40s-1200s.

[0031] The thickness of the pure metal layer and the high entropy amorphous alloy layer are the same, both of which are 5nm to 150nm.

[0032] Step 3: vacuum anneal the nano multilayer film to obtain a pure metal / high entropy amorphous alloy nano multilayer film with a three-dimensional interface.

[0033] During vacuum annealing of nano multilayer films, the vacuum degree of the furnace chamber is maintained at 10 -6 Pa, the degradation temperature is 423-513 K, the holding time is 1h, and during the annealing process, the temperature is gradually increased to 423-513 K, and the heating rate is 175-200K / h.

[0034] Magnetron sputtering technology can accurately control the composition of the component layer through the target material composition, accurately control the layer thickness of the component layer through the deposition time, and accurately control the microstructure of the component layer through parameters such as deposition pressure and temperature, thereby effectively controlling the microstructure of the nano multilayer film and affecting its deformation behavior and mechanical properties. When the thickness of the multilayer film is less than 5 nm, there is obvious interdiffusion between the component layers, and the composition is closer to the alloy film; when the thickness of the multilayer film is greater than 150 nm, its microstructure is almost the same as that of the multilayer film with a thickness of 150 nm, and the three-dimensional interface density obtained by heat treatment is low, so the optimal thickness range of the nano multilayer film is between 5nm and 150nm.

[0035] Vacuum heat treatment can change the interface state and the phase composition of the material, thereby affecting the mechanical properties of the material. When the annealing temperature is greater than 513 K, interdiffusion across the interface is likely to occur. When it is lower than 400 K, the interface morphology does not change significantly, so 473 K is selected as the heat treatment temperature. If the heating time is too fast, the mismatch stress is large and the film peels off. If the heating time or the holding time is too long, there is a risk of grain growth. Therefore, the heating rate is set to 175 K / h and the holding time is set to 1 h.

[0036] The present application is regulated by heat treatment, so that the pure metal / high entropy amorphous alloy nano multilayer film with a positive mixing enthalpy interface is mixed at the nanoscale, forming a medium-range ordered crystal / amorphous three-dimensional interface. When the dislocation is emitted from the dislocation source and completes the slip in the crystal layer, it will reach the three-dimensional interface. Different from the sharp two-dimensional interface, the three-dimensional interface has a certain strength, and the movement of the dislocation in this area will be affected by the stress, which then changes the status quo of the dislocation completing the slip and annihilation. The dislocations are arranged in an orderly manner near the three-dimensional interface, and then piled up. The long-range orderly dislocation arrangement significantly enhances the heterogeneous deformation stress and effectively improves the strength of the material. The mixing enthalpy between the pure metal layer and the high entropy amorphous alloy layer is positive, which can effectively reduce the degree of diffusion during the heat treatment process and maintain the thermal stability of the layered modulation structure. The low interface energy unique to the crystal / amorphous interface significantly heterogeneously migrates the crystal layer grain boundaries, so that the grains do not grow excessively.

[0037] For nano-multilayer films with a thickness of 10 nm, the ultra-high density of the crystal / amorphous interface is fully utilized, and the back stress is significantly increased. For nano-multilayer films with a thickness of 100 nm, the heterogeneous deformation stress is not significantly increased due to the lower interface density.

[0038] Example 1 A method for preparing a pure metal / high entropy amorphous alloy nano multilayer film with a three-dimensional interface comprises the following steps: First, the single crystal silicon substrate was ultrasonically cleaned in analytical pure acetone and anhydrous ethanol for 10 min each, and then quickly dried using a heater. Subsequently, it was immersed in 41 wt.% hydrofluoric acid for 5 min to remove the oxide film and then quickly dried. Secondly, the single crystal silicon substrate is fixed on the base plate and automatically transported into the magnetron sputtering vacuum coating chamber until the back vacuum degree is 4.0×10 -4 Pa.

[0039] Then, using Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 Alloy targets are sputtered alternately.

[0040] Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 The alloy target uses a DC power supply with a power of 200 W, the deposition gas pressure is set to 1.0 Pa, the deposition temperature is room temperature, and the substrate speed is 15 r / min. The Cu layer is first deposited for 17 s, followed by the high entropy amorphous alloy layer for 40 s. A total of 150 cycles are deposited to obtain a deposited pure metal / high entropy amorphous alloy nano-multilayer film. The surface of the nano-multilayer film is a high entropy amorphous alloy layer, the bottom layer is a Cu layer, and the thickness of the multilayer film is 1500nm.

[0041] Finally, the sample was naturally cooled in the high vacuum coating chamber for 2-3 hours to room temperature and then taken out for vacuum heat treatment. The deposition surface was placed upward in the furnace chamber and the temperature was raised to 473 K at a rate of 175 K / h. The temperature was kept for 1 hour and then cooled to room temperature with the furnace and taken out to obtain a nano-multilayer film with a three-dimensional crystal / amorphous interface with a layer thickness of 5 nm.

[0042] Example 2 A method for preparing a pure metal / high entropy amorphous alloy nano multilayer film with a three-dimensional interface comprises the following steps: First, the single crystal silicon substrate was ultrasonically cleaned in analytical pure acetone and anhydrous ethanol for 10 min each, and then quickly dried using a heater. Subsequently, it was immersed in 41 wt.% hydrofluoric acid for 5 min to remove the oxide film and then quickly dried.

[0043] Secondly, the single crystal silicon substrate is fixed on the base plate and automatically transported into the magnetron sputtering vacuum coating chamber until the back vacuum degree is 4.0×10 -4 Pa.

[0044] Then, using Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 Alloy targets are sputtered alternately.

[0045] Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 The alloy target uses a DC power supply with a power of 200 W, the deposition gas pressure is set to 1.0 Pa, the deposition temperature is room temperature, the substrate speed is 15 r / min, the Cu layer is deposited first, the deposition time is 34 s, and then the high entropy amorphous alloy layer is deposited, the deposition time is 80 s, and a total of 75 cycles are deposited to obtain a deposited pure metal / high entropy amorphous alloy nano-multilayer film. The surface of the nano-multilayer film is a high entropy amorphous alloy layer, and the bottom layer is a Cu layer. The thickness of the multilayer film is 1500nm.

[0046] Finally, the sample was naturally cooled in the high vacuum coating chamber for 2-3 hours to room temperature and then taken out for vacuum heat treatment. The deposition surface was placed upward in the furnace chamber and the temperature was raised to 473 K at a rate of 175 K / h. The temperature was kept for 1 hour and then the sample was cooled to room temperature and taken out to obtain a nano-multilayer film with a 10 nm thick dimensional crystal / amorphous interface.

[0047] The microstructure characterization and mechanical properties of the prepared multilayer films were tested, such as Figure 2-5 As shown, analysis of the XRD spectrum, SEM image and TEM image of the obtained nano-multilayer film with a layer thickness of 10 nm shows that the nano-multilayer film has a dual-phase structure, the crystal layer has an FCC structure, and the high-entropy alloy layer has a long-range disordered amorphous structure. Figure 3 The SEM image in the middle shows that the surface is flat after annealing and there is no cracking caused by thermal stress; Figure 4 The low-magnification TEM cross-sectional photograph in the figure shows that the layered modulation structure is maintained. The selected area electron diffraction pattern in the upper right corner proves that only the FCC structure exists in the crystal layer. Figure 5 The high-magnification TEM cross-sectional photos in the figure show that the interface between the two component layers is a three-dimensional staggered interface with a width of several atomic layers. Along the growth direction of the multilayer film, the crystal layer forms a single-crystal columnar structure, and there are no twins in the grains. The nanoindentation hardness was measured to be 6.04±0.12 GPa under a load of 6000 μN. The heterogeneous deformation stress of the multilayer film was tested by the cyclic indentation method. In the displacement control mode, the initial indentation depth was 10 nm, and then the indentation depth increased by 10 nm each time. After ten cycles of indentation, the heterogeneous deformation stress was measured to be 3.04±0.12 GPa. The above mechanical properties are significantly higher than those of the multilayer nanofilm with a two-dimensional interface.

[0048] Example 3 A method for preparing a pure metal / high entropy amorphous alloy nano multilayer film with a three-dimensional interface comprises the following steps: First, the single crystal silicon substrate was ultrasonically cleaned in analytical pure acetone and anhydrous ethanol for 10 min each, and then quickly dried using a heater. Subsequently, it was immersed in 41 wt.% hydrofluoric acid for 5 min to remove the oxide film and then quickly dried.

[0049] Secondly, the single crystal silicon substrate is fixed on the base plate and automatically transported into the magnetron sputtering vacuum coating chamber until the back vacuum degree is 4.0×10 -4 Pa.

[0050] Then, using Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 Alloy targets are sputtered alternately.

[0051] Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 The alloy target uses a DC power supply with a power of 200 W, the deposition gas pressure is set to 1.0 Pa, the deposition temperature is room temperature, the substrate rotation speed is 15r / min, the Cu layer is deposited first, the deposition time is 85 s, and then the high entropy amorphous alloy layer is deposited, the deposition time is 200 s, and a total of 30 cycles are deposited. The thickness of the multilayer film is 1500 nm.

[0052] Finally, the sample was naturally cooled in the high vacuum coating chamber for 3 hours to room temperature and then taken out for vacuum heat treatment. The deposition surface was placed upward in the furnace chamber and the temperature was raised to 473 K at a rate of 175 K / h. The temperature was kept for 1 hour and then cooled to room temperature with the furnace and taken out to obtain a nano-multilayer film with a three-dimensional crystal / amorphous interface with a layer thickness of 25 nm.

[0053] Example 4 A method for preparing a pure metal / high entropy amorphous alloy nano multilayer film with a three-dimensional interface comprises the following steps: First, the single crystal silicon substrate was ultrasonically cleaned in analytical pure acetone and anhydrous ethanol for 10 min each, and then quickly dried with a hair dryer. It was then immersed in 41 wt.% hydrofluoric acid for 5 min to remove the oxide film and then quickly dried.

[0054] Secondly, the single crystal silicon substrate is fixed on the base plate and automatically transported into the magnetron sputtering vacuum coating chamber until the back vacuum degree is 4.0×10 -4 Pa.

[0055] Then, using Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 Alloy targets are sputtered alternately.

[0056] Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 The alloy target uses a DC power supply with a power of 200 W, the deposition gas pressure is set to 1.0 Pa, the deposition temperature is room temperature, the substrate rotation speed is 15r / min, the Cu layer is deposited first, the deposition time is 170 s, and then the high entropy amorphous alloy layer is deposited, the deposition time is 400 s, and 15 cycles are deposited in total. The thickness of the multilayer film is 1500 nm.

[0057] Finally, the sample was naturally cooled in the high vacuum coating chamber for 3 hours to room temperature and then taken out for vacuum heat treatment. The deposition surface was placed upward in the furnace chamber and the temperature was raised to 473 K at a rate of 175 K / h. The temperature was kept for 1 hour and then cooled to room temperature with the furnace and taken out to obtain a nano-multilayer film with a three-dimensional crystal / amorphous interface with a layer thickness of 50 nm.

[0058] Example 5 A method for preparing a pure metal / high entropy amorphous alloy nano multilayer film with a three-dimensional interface comprises the following steps: First, the single crystal silicon substrate was ultrasonically cleaned in analytical pure acetone and anhydrous ethanol for 10 min each, and then quickly dried with a hair dryer. It was then immersed in 41 wt.% hydrofluoric acid for 5 min to remove the oxide film and then quickly dried.

[0059] Secondly, the single crystal silicon substrate is fixed on the base plate and automatically transported into the magnetron sputtering vacuum coating chamber until the back vacuum degree is 4.0×10 -4 Pa.

[0060] Then, using Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 Alloy targets are sputtered alternately.

[0061] Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 The alloy target uses a DC power supply with a power of 200 W, the deposition gas pressure is set to 1.0 Pa, the deposition temperature is room temperature, the substrate rotation speed is 15 r / min, the Cu layer is deposited first, the deposition time is 340 s, and then the high entropy amorphous alloy layer is deposited, the deposition time is 800 s, and a total of 8 cycles are deposited, and the thickness of the multilayer film is 1600 nm.

[0062] Finally, the sample was naturally cooled in the high vacuum coating chamber for 3 hours to room temperature and then taken out for vacuum heat treatment. The deposition surface was placed upward in the furnace chamber and the temperature was raised to 473 K at a rate of 175 K / h. The temperature was kept for 1 hour and then cooled to room temperature with the furnace and taken out to obtain a nano-multilayer film with a three-dimensional crystal / amorphous interface with a layer thickness of 100 nm.

[0063] The prepared Cu / Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 Microstructure characterization and mechanical properties testing of multilayer films, such as Figure 2 and Figure 6-8 As shown, the obtained Cu / Fe layer with a thickness of 100 nm 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17The XRD spectrum, SEM image and TEM image of the nano multilayer film show that Cu / Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 The nano-multilayer film has a dual-phase structure, the crystal layer has an FCC structure, and the high-entropy alloy layer has a long-range disordered amorphous structure. Figure 6 The SEM image in the middle shows that the surface is flat after annealing, without cracking and peeling caused by thermal stress; Figure 7 The low-magnification TEM cross-sectional photograph in the figure shows that the layered modulation structure is maintained. The selected area electron diffraction pattern in the upper right corner proves that only the FCC structure exists in the crystal layer. Figure 8 The high-magnification TEM cross-sectional photograph in the figure shows that the interface between the two component layers is a three-dimensional staggered interface with a width of several atomic layers. Along the growth direction of the multilayer film, the crystal layer forms a single-crystal columnar structure, and there are no twins in the grains. The nanoindentation hardness was measured to be 4.92±0.19 GPa under a load of 6000 μN. The heterogeneous deformation stress of the multilayer film was tested by the cyclic indentation method, with a displacement control mode, an initial indentation depth of 10 nm, and then an indentation depth increase of 10 nm each time. After ten cycles of indentation, the heterogeneous deformation stress was measured to be 2.38±0.11 GPa.

[0064] Example 6 A method for preparing a pure metal / high entropy amorphous alloy nano multilayer film with a three-dimensional interface comprises the following steps: First, the single crystal silicon substrate was ultrasonically cleaned in analytical pure acetone and anhydrous ethanol for 10 min each, and then quickly dried with a hair dryer. It was then immersed in 41 wt.% hydrofluoric acid for 5 min to remove the oxide film and then quickly dried.

[0065] Secondly, the single crystal silicon substrate is fixed on the base plate and automatically transported into the magnetron sputtering vacuum coating chamber until the back vacuum degree is 4.0×10 -4 Pa.

[0066] Then, using Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 Alloy targets are sputtered alternately.

[0067] Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si17 The alloy target uses a DC power supply with a power of 200 W, the deposition gas pressure is set to 1.0 Pa, the deposition temperature is room temperature, the substrate rotation speed is 15r / min, the Cu layer is deposited first, the deposition time is 510 s, and then the high entropy amorphous alloy layer is deposited, the deposition time is 1200 s, and 5 cycles are deposited in total. The thickness of the multilayer film is 1500 nm.

[0068] Finally, the sample was naturally cooled in the high vacuum coating chamber for 3 hours to room temperature and then taken out for vacuum heat treatment. The deposition surface was placed upward in the furnace chamber and the temperature was raised to 473 K at a rate of 175 K / h. The temperature was kept for 1 hour and then cooled to room temperature with the furnace and taken out to obtain a nano-multilayer film with a three-dimensional crystal / amorphous interface with a layer thickness of 150 nm.

[0069] Example 7 The difference between this embodiment and embodiment 6 lies in the sputtering process and the annealing process, and the other steps are the same.

[0070] A method for preparing a pure metal / high entropy amorphous alloy nano multilayer film with a three-dimensional interface comprises the following steps: Using Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 Alloy targets are sputtered alternately.

[0071] Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 The alloy target uses a DC power supply with a power of 200 W, the deposition gas pressure is set to 0.8 Pa, the deposition temperature is room temperature, the substrate rotation speed is 15 r / min, the Cu layer is deposited first, the deposition time is 510 s, and then the high entropy amorphous alloy layer is deposited, the deposition time is 1200 s, and 5 cycles are deposited in total. The thickness of the multilayer film is 1500 nm.

[0072] The multilayer film was naturally cooled in the high vacuum coating chamber for 3 hours to room temperature and then taken out. Subsequently, it was subjected to vacuum heat treatment. The deposited surface was placed upward in the furnace chamber and the temperature was raised to 513 K at a rate of 180 K / h. The temperature was kept for 1 hour and then the film was cooled to room temperature and taken out to obtain a nano-multilayer film with a layer thickness of 150 nm and a three-dimensional crystal / amorphous interface.

[0073] Example 8 A method for preparing a pure metal / high entropy amorphous alloy nano multilayer film with a three-dimensional interface comprises the following steps: Using Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 Alloy targets are sputtered alternately.

[0074] Cu target and Fe 15.6 Co 14.4 Cr 15.9 Ni 14.1 B 23 Si 17 The alloy target uses a DC power supply with a power of 200 W, the deposition gas pressure is set to 0.9 Pa, the deposition temperature is room temperature, the substrate rotation speed is 15 r / min, the Cu layer is deposited first, the deposition time is 510 s, and then the high entropy amorphous alloy layer is deposited, the deposition time is 1200 s, and 5 cycles are deposited in total. The thickness of the multilayer film is 1500 nm.

[0075] The multilayer film was naturally cooled in the high vacuum coating chamber for 3 hours to room temperature and then taken out. Subsequently, it was subjected to vacuum heat treatment. The deposited surface was placed upward in the furnace chamber and the temperature was raised to 423K at a rate of 200 K / h. The temperature was kept for 1 hour and then cooled to room temperature with the furnace and taken out to obtain a nano-multilayer film with a layer thickness of 150 nm and a three-dimensional crystal / amorphous interface.

[0076] The present application provides a method for preparing a pure metal / high entropy amorphous alloy nano-multilayer film with a three-dimensional interface. The pure metal / high entropy alloy nano-multilayer film is prepared by depositing it on a clean silicon substrate by a magnetron sputtering deposition method. First, the single crystal silicon substrate is cleaned by ultrasonic vibration, and the oxide film on the surface of the single crystal silicon substrate is removed by a hydrofluoric acid solution so that the atoms in the film and the substrate silicon are directly bonded, which is beneficial to improve the bonding force between the multilayer film and the substrate. Ar gas is ionized to generate Ar+ ions, which are accelerated to bombard the cathode target (metal Cu and high entropy amorphous alloy) under the action of the electric field force, and the target atoms and secondary electrons are sputtered out, wherein the target atoms are deposited on the anode substrate in the opposite direction, and the movement direction of the secondary electrons in the electromagnetic field is perpendicular to the electric field and the magnetic field, presenting a circular rolling line motion trajectory, thereby enhancing the frequency of collision with Ar atoms and improving the ionization rate of Ar atoms. The present invention adopts magnetron sputtering technology to alternately deposit metal Cu targets and high entropy amorphous alloy targets, and both adopt a DC power of 200 W, the working temperature is low, the amorphous structure is maintained, and the thickness of the pure metal layer and the high entropy amorphous alloy layer can be effectively controlled by the deposition time. Natural cooling to room temperature in a high vacuum chamber effectively avoids peeling caused by the difference in thermal expansion coefficients between the film member layers and the film base. At the same time, it prevents the film from contacting with air under high temperature and causing oxidation, so that the deposited atoms can fully diffuse to form a metal / high entropy amorphous alloy nano-multilayer film.

[0077] like Figures 1 to 10 As shown in the figure, controlling the deposition time during magnetron sputtering can obtain pure metal / high entropy amorphous alloy nano-multilayer films of different layer thicknesses, and controlling the heating rate and holding time during annealing can regulate the interface morphology. Through the careful design of deposition process parameters and annealing process parameters, a crystal / high entropy amorphous alloy nano-multilayer film with a three-dimensional interface is effectively designed, and the interface dislocation storage capacity and hardness are further enhanced, effectively improving the service performance of the material.

[0078] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A three-dimensional interface pure metal / high entropy amorphous alloy nano multilayer film, characterized in that: It includes alternately stacked crystal layers and amorphous layers, the crystal layers are single-phase face-centered cubic structures, the grains are columnar crystals that grow along the deposition direction and penetrate the component layers, the amorphous layers maintain a long-range disordered structure, and the interface between the crystal layers and the amorphous layers is a three-dimensional structure.

2. The three-dimensional interface pure metal / high entropy amorphous alloy nano multilayer film according to claim 1, characterized in that: The bottom layer of the nano multilayer film is a crystal layer, and the surface layer is an amorphous layer.

3. The three-dimensional interface pure metal / high entropy amorphous alloy nano multilayer film according to claim 1, characterized in that: The thickness of the crystal layer and the amorphous layer is equal, and the layer thickness is 5nm to 150nm.

4. The three-dimensional interface pure metal / high entropy amorphous alloy nano multilayer film according to claim 1, characterized in that: The crystalline layer is copper, and the amorphous layer is FeCoCrNiBSi alloy.

5. A three-dimensional interface pure metal / high entropy amorphous alloy nano multilayer film according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1, cleaning the substrate surface; Step 2: In a vacuum environment, a pure metal target and a high entropy amorphous alloy target are alternately used to perform DC magnetron sputtering on the substrate, and after cooling, a deposited pure metal / high entropy amorphous alloy nano multilayer film is obtained; The sputtering power is 200 W, the deposition gas pressure is 0.8-1 Pa, the sputtering time of the pure metal target in each sputtering cycle is 17s-510s, and the sputtering time of the high entropy amorphous alloy target is 40s-1200s; Step 3: vacuum annealing the obtained nano multilayer film to obtain a pure metal / high entropy amorphous alloy nano multilayer film with a three-dimensional interface.

6. The three-dimensional interface pure metal / high entropy amorphous alloy nano multilayer film according to claim 5, characterized in that: The cleaning process includes cleaning the surface of the substrate and removing the oxide film on the surface.

7. The three-dimensional interface pure metal / high entropy amorphous alloy nano multilayer film according to claim 5, characterized in that: During the magnetron sputtering, the rotation speed of the silicon substrate is 15 r / min.

8. The three-dimensional interface pure metal / high entropy amorphous alloy nano multilayer film according to claim 5, characterized in that: The method of the vacuum annealing is as follows: The temperature was gradually raised to 423-513 K, kept at that temperature for 1 h, and then cooled to room temperature in the furnace.

9. The three-dimensional interface pure metal / high entropy amorphous alloy nano multilayer film according to claim 8, characterized in that: The heating rate is 175-200 K / h.

10. The three-dimensional interface pure metal / high entropy amorphous alloy nano multilayer film according to claim 8, characterized in that: The pure metal target is a copper target, and the high entropy amorphous alloy target is a FeCoCrNiBSi alloy target.

Citation Information

Patent Citations

  • Method for preparing nanocrystalline / amorphous metal multi-layer film plastification through double-groove electrolysis

    CN106086963A

  • Preparation method of metal / amorphous alloy diffusion couple

    CN108588588A

  • Preparation method of multilayer heterostructure high-entropy alloy

    CN111471957A

  • Method for predicting strength of high-entropy alloy with double-phase structure

    CN113393912A

  • Metal ceramic spectrum selective absorbing coating with dual composite nano microstructure and preparation method thereof

    CN118957496A

Cited By

  • Titanium-based high-entropy amorphous / tungsten multilayer film with anti-irradiation and low-hydrogen retention potential and preparation method and application of titanium-based high-entropy amorphous / tungsten multilayer film

    CN120291038A